Pasien Wanita 41 Tahun dengan Sindrom Hipersensitivitas Obat (SHO) akibat Antibiotik - Purba, Kevin Jeremia; Angraini, Dwi Indria (Medula, 2025)
Aberrant reactions to drugs vary, ranging from mild to severe clinical symptoms. Drug Hypersensitivity Syndrome (SHO) is a systemic autoimmune disorder caused by aberrant reactions to drugs which can cause symptoms in the form of skin eruptions, fever accompanied by involvement of one or several internal organs. Drug Hypersensitivity Syndrome is often caused by drugs such as trimethoprim, allopurinol, metronidazole, dapsone and abacavir. This disease can also occur due to cross-reaction of drugs, such as anti-convulsant drugs (carbamazepine, phenytoin, phenobarbital) and non-steroidal anti-inflammatory drugs (piroxicam). Reported on a 41 year old female patient with complaints including: the main complaint was red spots accompanied by itching all over the body and yellowing of both eyes. Clinical symptoms appeared after the patient consumed various types of drugs in the last two weeks. Investigation revealed thrombocytopenia and a drastic increase in liver enzymes. Based on the physical and supporting examination, a diagnosis of Drug Hypersensitivity Syndrome et causa susp was made. amoxicillin. The main management of SHO is identification and stopping the causative drug, symptomatic therapy and recommended administration of systemic corticosteroids.